2023
DOI: 10.14218/jcth.2022.00301
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA Synthetase-based Prognosis Model and Exploration of Potential Mechanisms in Hepatocellular Carcinoma

Abstract: Background and Aims:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Mutations in YARS1 have been associated with some hereditary neurodevelopmental and multisystem disorders [20,21]. Jin et al showed that aminoacyl-tRNA synthetases (ARS) can participate in tumorigenesis and progression, and that the HCC prognosis model based on the ARS family is effective [22].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in YARS1 have been associated with some hereditary neurodevelopmental and multisystem disorders [20,21]. Jin et al showed that aminoacyl-tRNA synthetases (ARS) can participate in tumorigenesis and progression, and that the HCC prognosis model based on the ARS family is effective [22].…”
Section: Discussionmentioning
confidence: 99%